2012
DOI: 10.1136/ejhpharm-2012-000074.344
|View full text |Cite
|
Sign up to set email alerts
|

Synergic antifungal and antibacterial activity of alcoholic extract of the species Robinia pseudoacacia L. (Fabaceae)

Abstract: Background Plant species Robinia pseudoacacia L. (Fabaceae) has been used as a medicinal plant since ancient times, as its infusions and extracts have antacid, antibacterial, purgative and emenagogic properties. The volatile oil of the flowers is also used in perfumery and cosmetics. Purpose Due to its high content of volatile oil phenolic compounds, flavonoids and tannins with antimicrobial properties, the present study proposed to investigate the antibacterial and antifungal effect of the species Robinia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…In addition, the 70 % ethanol solvent control showed some activity against K. pneumoniae strains, A. baumannii and Candida sp. These results are in accordance with literature data, i.e., a 90 % ethanolic extracts of R. pseudoacacia leaves and barks were shown to be active against E. coli, P. aeruginosa, Proteus vulgaris, Salmonella choleraesuis and C. albicans strains 27. …”
supporting
confidence: 93%
“…In addition, the 70 % ethanol solvent control showed some activity against K. pneumoniae strains, A. baumannii and Candida sp. These results are in accordance with literature data, i.e., a 90 % ethanolic extracts of R. pseudoacacia leaves and barks were shown to be active against E. coli, P. aeruginosa, Proteus vulgaris, Salmonella choleraesuis and C. albicans strains 27. …”
supporting
confidence: 93%
“…Further, Gurudeeban et al [ 16 ] reported high antibacterial activity of the methanolic extracts of C. colocynthis fruits against bacteria, such as B. subtilis , Streptococcus pyogenes , and Salmonella typhi . Robinin extracted from Robinia pseudoacacia L. has high antibacterial activity [ 55 , 56 ]. Benzoic acid and its derivatives have antibacterial activities and might be used as food preservatives [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of most microorganisms, it is reported that their growth was inhibited by concentration of 2.00 mg/mL. Rosu et al [34] reported that extracts from different parts of the plant had different antibacterial activities. Extracts of false acacia flowers and seeds were efficient antibacterials for Gram positive cocci.…”
Section: Microbiological Analysesmentioning
confidence: 99%